The Coronavirus pandemic – 2022: Viruses, variants & vaccines. (February 2022) - Alexandridi, Magdalini; Mazej, Julija; Palermo, Enrico; Hiscott, John
Abstract: Since the beginning of the COVID-19 pandemic in 2019–2020, Cytokine & Growth Factor Reviews has published several Special Issues focused on the biology, pathogenesis and therapeutic options in the treatment of COVID-19 infection, including articles on the involvement of the chemokine system in the cytokine storm in COVID-19, intervention in the early stages of COVID-19 pneumonia, the therapeutic value of corticosteroid treatment, early clinical intervention with type 1 interferons, progress in vaccine development, and organ specific complications of COVID-19. By 2022, multiple highly efficacious vaccines are available and are being administered in countries around the world, therapeutic options have been clinically evaluated and approved, and SARS-CoV-2 has arguably become the most thoroughly studied virus in history. But, with progress has also come unanticipated problems – misinformation, anti-vaxxers, opposition to protective masks, and politically motivated interference disguised as knowledge. With this issue of CGFR, we continue to document the global coronavirus pandemic and provide an update on the emergence of viral variants, the global effort to administer vaccines and the impediments to progress posed by misinformation and anti-vaccine sentiment.